A Comprehensive Ahp-Topsis Approach For Non-Traditional Machining Process Selection In The Manufacturing Sector - Bhupendra Lovanshi; Raji N. Mishra (International Journal of Manufacturing and Production Engineering, 2024)
Non-traditional machining processes (NTMPs) are being used more widely in modern industry as a result of the increased use of advanced materials in that sector. Selecting the best Non-Traditional Machining Process (NTMP) is essential to a manufacturing company's success and competitiveness. One way to think of the process of choosing the best NTMP for a given machining processes application is as a multi-criteria decision-making (MCDM) problem with a lot of competing criteria. The present study unveils a combination of two MCDM strategies for addressing NTMP selection: the procedure for Preference for Order by Similarity to the Perfect Solution (TOPSIS) method. To assess the relative significance of the quality criteria considered, a pairwise comparison matrix of the Analytic Hierarchy Process (AHP) is utilized. The results obtained through the Order Preference by Comparison to Ideal Solution (TOPSIS) method show how this the MCDM method strategy can be used to solve complex NTMP select problems.
Keywords: Non-traditional machining processes (NTMP); Technique for order preference by similarity to ideal solution (TOPSIS); analytical hierarchy process (AHP); multi criteria decision Making (MCDM)